MENINGKATKAN KEMAMPUAN KERJASAMA SISWA MELALUI PERMAINAN ESTAFET BOLA DI KELOMPOK A KB BUAH HATI KECAMATAN KENDURUAN KABUPATEN TUBAN - Novitasari, Nurul; Rianik, Rianik; Fitri, Lailatul (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
The cooperative ability of students in group A KB Buah Hati has not developed well. There are students who are still fighting over toys, lack of focus when counting relays, don't want to queue to wait their turn, don't want to help their friends in the game if they need help, and students prefer to play alone. The research, which was conducted in group A KB Buah Hati, aims to improve students' collaboration skills through the ball relay game. The problems examined in this study are about 1) how to improve students' cooperation skills through the ball relay game, 2) how is the effectiveness of the ball relay game to improve student collaboration skills in group A KB Buah Hati District Kenduruan. The type of research used is descriptive qualitative research. The method of data collection is through observation, interviews and documentation. The results of the study show, 1) efforts to improve students' cooperation skills are to apply the principle of learning while playing, through the ball relay game. 2) the implementation of the ball relay game is very effective in increasing student cooperation, it can be seen from the increase in cooperation skills after 3 ball relay games have been carried out.